Explaining Turnover Intention among Generation Z Contract Employees through Psychological, Physical, and Social Capital: Evidence from the Telecommunications BPO Industry - Haq, Zihaul; Wulansari, Puspita (International Journal of Indonesian Business Review, 2026)
Purpose – Employee turnover has become a major human resource challenge in the telecommunications Business Process Outsourcing (BPO) industry, particularly among Generation Z contract employees. This study examines the effects of psychological capital, physical capital, and social capital on turnover intention, with job satisfaction as a mediating variable. Methodology/approach – A quantitative explanatory approach was employed using survey data collected from 338 Generation Z employees working under fixed-term employment contracts in the telecommunications division of BPO Company XYZ. Respondents were selected through purposive sampling. Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 was utilized to assess both direct and indirect relationships among the proposed constructs. Findings – The results indicate that psychological capital, physical capital, and social capital significantly enhance job satisfaction, with physical capital exerting the strongest effect. Job satisfaction significantly reduces turnover intention and mediates the relationships between all three forms of capital and turnover intention. The model explains 63.2% of the variance in job satisfaction and 51.5% of the variance in turnover intention. Descriptive findings further highlight career opportunity, trust, work facilities, optimism, and resilience as priority areas for improving employee retention. Novelty – This study contributes to the Human Resource Management and Organizational Behavior literature by proposing an integrated model that examines psychological, physical, and social capital simultaneously as antecedents of turnover intention through the mediating role of job satisfaction. It also provides empirical evidence from Generation Z contract employees in the telecommunications BPO industry, offering a more comprehensive perspective on employee retention strategies.